Design of a Compact Electromagnetic Undulator for THz Radiation Production - Thaijai-Un K. (2017)
© 2016 The Authors. The goal of this research is to design a compact electromagnetic undulator. This insertion device will be installed at the PBP-CMU-LINAC system of Chiang Mai University (CMU), Thailand, to produce THz radiation. The undulator magnet is designed by using 2D POISSON and 3D RADIA computer code to optimize the magnet dimensions. The width of iron pole (w) should be 12 - 14 mm. The height of iron pole (L) should be about 85 mm long. The thickness of return yoke should be more than 10 mm and the lateral width (T) should be at least 50 mm. With the undulator period length of 56 mm, a 10 MeV electron beam is expected to produce THz radiation varying from 110 μm at K = 1 to 76 μm at K = 0.3.